Dinamika Pengelolaan Zakat Oleh Negara Di Beberapa Provinsi Di Indonesia Pasca Undang-Undang No. 23 Tahun 2011 - Aziz, Muhammad Izzuddin Abdul; Susetyo, Heru (UI Scholars Hub, 2019)
This article is derived from research conducted by the authors in some provinces in Indonesia. The focus of the research is the administration of zakat (alms) by the state, in this case, is BAZNAS at various provinces in Indonesia in the aftermath of Law No. 23/ 2011 on Zakat Administration. The authors select two provinces where Muslim inhabitants are a minority, namely in North Sulawesi and East Nusa Tenggara (NTT) and three provinces where Muslims are majority namely in Aceh, West Nusa Tenggara, and Gorontalo. There is three focus of questions: 1. The practice of zakat administration by the BAZNAS; 2. The performance of BAZNAS; and 3. The practice of zakat administration by non-state actors in selected provinces. The findings of this research are: the performance of zakat administration is very dependent on the number of zakat administrators (amil) and zakat payer, the professionalism of BAZNAS and legislation support from the provincial government through a specific local ordinance on zakat.